Konsumsi Garam sebagai Faktor Determinan Grade Hipertensi pada Penderita Hipertensi Primer di Wilayah Pesisir - FX. Ady Soesetijo; Krish Naufal Anugrah Robby; Ancah Caesarina Novi Marchianti (Multidisciplinary Journal, 2018)
Patients with essential hypertension in the coastal area is very vulnerable to having complications due to high consumption of salt habits. The purpose of this research was to know the effect consumption of salt on grade hypertension in essential hypertension patients in coastal area. This research was kuntitatif with observational analyzed method with cross sectional design. Sample of this research were 100 patient in kedungrejo public health center who taken by consecutive sampling. Partial Least Square (PLS) with smart PLS 3 Aplication software was used as to analyze data. Based on the test result there was positive influence of consumsion salt on grade hipertensi, T statistic was 75,234 (t statistic > t table significant 1.96) it meant Consumption of salt has positive effect on grade hypertension, high consumption of salt will be high grade hypertension. So it can be concluded that it is necessary to modify the behavior consumption of salt to reduce grade hypertension in essential hypertension patients of coastal community.Keywords: Consumption of salt, essential hypertension, grade hypertensi